Neuroprotective Effects of Annexin A1 Tripeptide after Deep Hypothermic Circulatory Arrest in Rats - Zhang, Zhiquan; Ma, Qing; Shah, Bijal; Mackensen, G. Burkhard; Lo, Donald C.; Mathew, Joseph P.; Podgoreanu, Mihai V.; Terrando, Niccolò (Frontiers in Immunology, 2017)
Resolution agonists, including lipid mediators and peptides such as annexin a1 (ANXA1), are providing novel approaches to treat inflammatory conditions. Surgical trauma exerts a significant burden on the immune system that can affect and impair multiple organs. Perioperative cerebral injury after cardiac surgery is associated with significant adverse cerebral outcomes such as delirium and postoperative cognitive dysfunction. Using a clinically relevant rat model of cardiopulmonary bypass (CPB) with deep hypothermic circulatory arrest (DHCA), we tested the pro-resolving effects of a novel bioactive ANXA1 tripeptide (ANXA1sp) on neuroinflammation and cognition. Male rats underwent 2 hour CPB with 1 hour DHCA at 18°C, and received vehicle or ANXA1sp followed by timed reperfusion up to postoperative day 7. Immortalized murine microglial cell line BV2 were treated with vehicle or ANXA1sp, and subjected to 2 hours oxygen-glucose deprivation followed by timed reoxygenation. Microglial activation, cell death, neuroinflammation, and NF-kB activation were assessed in tissue samples and cell cultures. Rats exposed to CPB and DHCA had evident neuroinflammation in various brain areas. However, in ANXA1sp-treated rats, microglial activation and cell death (apoptosis and necrosis) were reduced at 24 hours and 7 days after surgery. This was associated with a reduction in key pro-inflammatory cytokines due to inhibition of NF-κB activation in the brain and systemically. Treated rats also had improved neurologic scores and shorter latency in the Morris water maze. In BV2 cells treated with ANXA1sp, similar protective effects were observed including decreased pro-inflammatory cytokines and cell death. Notably, we also found increased expression of ANXA1, which binds to NF-κB p65 and thereby inhibits its transcriptional activity. Our findings provide evidence that treatment with a novel pro-resolving ANXA1 tripeptide is neuroprotective after cardiac surgery in rats by attenuating neuroinflammation, and may prevent postoperative neurologic complications.